1989
DOI: 10.1007/bf00331274
|View full text |Cite
|
Sign up to set email alerts
|

α-Factor leader sequence-directed transport of Escherichia coli β-galactosidase in the secretory pathway of Saccharomyces cerevisiae

Abstract: The construction of two fused genes is described. One involves the in-frame fusion of the yeast prepro-alpha-factor coding sequence, and the Escherichia coli lac Z gene. The second gene fusion utilizes a 103 bp yeast invertase NH2-terminal coding sequence at the fusion junction of the hybrid gene described above. The gene fusions, under the control of the alpha-factor promoter, expressed active beta-galactosidase in alpha haploid yeast cells. The activity could be regulated in a temperature-sensitive sir3 muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Plasmid pFMD13OAp (9 kb) contained the aprotinin gene sequence flanked by an a-leader gene and a terminator sequence (4,39). Plasmid p707 (8.4 kb), obtained from H. Wehlmann, Wuppertal, Germany, and maintained in Saccharomyces cerevisiae WHL292 or in E. coli HB101, is a derivative of pJS212 (6) with the aprotinin gene including the a-leader region and a terminator region inserted into the plasmid. E. coli cells were grown in Luria-Bertani (LB) broth (21); C. glutamicum pUN1 was cultivated in a modified LB inedium (tryptone, 8 g/liter [Oxoid, Unipath Ltd., Basingstoke, Hampshire, England]; Bacto Yeast Extract, S g/liter [Oxoid]; NaCl, 2.5 g/liter; pH 7.0).…”
Section: Methodsmentioning
confidence: 99%
“…Plasmid pFMD13OAp (9 kb) contained the aprotinin gene sequence flanked by an a-leader gene and a terminator sequence (4,39). Plasmid p707 (8.4 kb), obtained from H. Wehlmann, Wuppertal, Germany, and maintained in Saccharomyces cerevisiae WHL292 or in E. coli HB101, is a derivative of pJS212 (6) with the aprotinin gene including the a-leader region and a terminator region inserted into the plasmid. E. coli cells were grown in Luria-Bertani (LB) broth (21); C. glutamicum pUN1 was cultivated in a modified LB inedium (tryptone, 8 g/liter [Oxoid, Unipath Ltd., Basingstoke, Hampshire, England]; Bacto Yeast Extract, S g/liter [Oxoid]; NaCl, 2.5 g/liter; pH 7.0).…”
Section: Methodsmentioning
confidence: 99%
“…In E. coli, the attempt to direct β-galactosidase to the membrane using the signal sequence of a membranar protein (lamb) was ineffective. 43 In S. cerevisiae, different signal sequences have been tried, namely from the SUC2, 44 MFα 45 and STA2, 46 genes, but these attempts were also unsuccessful. With the STA2 signal sequence the authors were able to detect 76% of β-galactosidase activity in the periplasmatic space but no enzyme activity was detected in the culture medium.…”
Section: Gal4mentioning
confidence: 99%
“…MFal, encoding the M F a l leader region that ends in the Lys-Arg-(Glu-Ala)2 hexapeptide (Kurjan and Herskowitz 1982;Filho et al 1986;Das et al 1989), has been shown to be generally useful for the secretion of heteroiogous proteins in yeast (Bitter et al 1989). However, since different proteins are secreted with different efficiencies, it has been speculated that the character of the protein fused to the M F a l leader region is likely to affect the secretion efficiency (Miyajima et al 1985(Miyajima et al , 1986Zsebo et al 1986).…”
Section: Discussionmentioning
confidence: 99%